2017
DOI: 10.3389/fpsyg.2017.01954
|View full text |Cite
|
Sign up to set email alerts
|

Eye Contact and Fear of Being Laughed at in a Gaze Discrimination Task

Abstract: Current approaches conceptualize gelotophobia as a personality trait characterized by a disproportionate fear of being laughed at by others. Consistently with this perspective, gelotophobes are also described as neurotic and introverted and as having a paranoid tendency to anticipate derision and mockery situations. Although research on gelotophobia has significantly progressed over the past two decades, no evidence exists concerning the potential effects of gelotophobia in reaction to eye contact. Previous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 50 publications
5
15
1
Order By: Relevance
“…This dissociation is difficult to reconcile with the domain-general view of attentional processes. The opposite congruency effects for gaze and arrows have been replicated in subsequent experiments in our laboratory (Roman-Caballero, Marotta, Martin-Arevalo, & Lupiañez, 2017), and other studies have found that the reversed congruency effect is modulated by the emotional expression of a face when the whole face instead of just the eyes is used as the target (Jones, 2015;Torres-Marín, Carretero-Dios, Acosta, & Lupiáñez, 2017), thus supporting the social nature of the effect.…”
Section: Discussionsupporting
confidence: 70%
“…This dissociation is difficult to reconcile with the domain-general view of attentional processes. The opposite congruency effects for gaze and arrows have been replicated in subsequent experiments in our laboratory (Roman-Caballero, Marotta, Martin-Arevalo, & Lupiañez, 2017), and other studies have found that the reversed congruency effect is modulated by the emotional expression of a face when the whole face instead of just the eyes is used as the target (Jones, 2015;Torres-Marín, Carretero-Dios, Acosta, & Lupiáñez, 2017), thus supporting the social nature of the effect.…”
Section: Discussionsupporting
confidence: 70%
“…This surprising result was opposite to the classical spatial Stroop effect generally observed with non-social stimuli like arrows or words (e.g., faster reaction time for congruent conditions; Lu & Proctor, 1995). Other research groups have replicated this reversed congruency effect (Edwards et al, 2020;Jones, 2015), and further investigation has revealed that this effect is found both when eyes were embedded in a whole face (Jones, 2015;Torres-Marín et al, 2017) or presented alone (Cañadas & Lupiáñez, 2012), and is modulated by the emotional expression of the face (Jones, 2015;Torres-Marín et al, 2017).…”
contrasting
confidence: 57%
“…For example, there is conflicting evidence regarding how approach and avoidance emotions in the gazing face affects the processing of off-centre inward gaze (cf. Jones, 2015; Torres-Marín, Carretero-Dios, Acosta, & Lupiáñez, 2017). Furthermore, Torres-Marin et al (2017) found that participants’ level of Gelotophobia (fear of being laughed at), which should relate to the sensitivity to direct gaze, did not affect gaze identification in a paradigm similar to that used here.…”
Section: Discussionmentioning
confidence: 99%
“…Jones, 2015; Torres-Marín, Carretero-Dios, Acosta, & Lupiáñez, 2017). Furthermore, Torres-Marin et al (2017) found that participants’ level of Gelotophobia (fear of being laughed at), which should relate to the sensitivity to direct gaze, did not affect gaze identification in a paradigm similar to that used here. Taken together with our demonstration of the importance of the looked-at object, it therefore appears that the misattribution of direct gaze can no longer account for these interesting data.…”
Section: Discussionmentioning
confidence: 99%